2018
DOI: 10.30848/pjb2019-2(12)
|View full text |Cite
|
Sign up to set email alerts
|

Influence of deficit irrigation, sowing methods and mulching on yield components and yield of wheat in semiarid environment

Abstract: Water scarcity is one of the leading crop limiting factor in the modern world of farming. Improving water use efficiency is one of the most serious challenge for agricultural scientists and water management experts. To evaluate the influence of sowing methods and mulch on wheat water productivity under deficit irrigation, experiments were conducted over a period of two years (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 6 publications
1
5
0
1
Order By: Relevance
“…of spikes/m 2 and grain weight/spike and its main components (number of grains/spike and 1000 grain weight) as previously discussed in Table 6. Similar results were attained by other investigators who found that exposing wheat plants to drought stress by decreasing number of irrigation from 5 to 4 or 3 times caused a reduction in grain and biological yields/ha as reported by Soomro et al (2016) and Razaq et al (2016). Moreover, El found that exposing wheat plants to drought stress at stem elongation, booting and/or flowering stages decreased straw yield/fad compared to full irrigation.…”
Section: The Data Insupporting
confidence: 89%
See 1 more Smart Citation
“…of spikes/m 2 and grain weight/spike and its main components (number of grains/spike and 1000 grain weight) as previously discussed in Table 6. Similar results were attained by other investigators who found that exposing wheat plants to drought stress by decreasing number of irrigation from 5 to 4 or 3 times caused a reduction in grain and biological yields/ha as reported by Soomro et al (2016) and Razaq et al (2016). Moreover, El found that exposing wheat plants to drought stress at stem elongation, booting and/or flowering stages decreased straw yield/fad compared to full irrigation.…”
Section: The Data Insupporting
confidence: 89%
“…The superiority of growth traits, total chlorophyll and phenological development stages obtained herein at full irrigation regime (five irrigations) may be due to that the sufficient soil moisture in the root zone help the plants to absorb greater amount of water and nutrients which enhancing internodes elongation and cell division as well as improving pigments and photosynthetic process and metabolites accumulation and consequently increased growth periods. In this concern, many researchers reported that providing the wheat plants with sufficient moisture caused an increase in plant height (Razaq et al, 2016, Soomro et al, 2016, flag leaf area (El-Metwally et al, 2015), chlorophyll (Abdelraouf et al, 2013 andAl-Ghzawi et al, 2018) and days from sowing till heading and maturity Mekkei &El Haggan, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Whilst full irrigation showed a tendency to reduce grain weight and stimulate straw weight in our study (data not shown), a significant difference (p ≤ 0.05) in straw weight was only found between WW and FD plants (when O 3 treatments were pooled; O 3 did not affect straw weight). Under semi-arid environmental conditions in Pakistan, 20% DI in combination with raised bed cultivation and mulching improved wheat yield [31]. Other field studies have shown that wheat yield [32,33] was not significantly affected at 25–30% DI compared to full irrigation.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced g s will lead to a reduced O 3 uptake, hence AWD might also be beneficial for mitigating the adverse impacts of O 3 on rice yield. Similarly, reduced irrigation of wheat either stimulated both yield and crop water use efficiency (WUE) [29,30,31] or stimulated WUE without a yield penalty [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…Deneme yılı olan 2021 yılı kurak geçtiğinden (Tablo 1) düz ekimlere oranla sırt ekimlerde toprak neminin daha iyi muhafaza edildiği belirlenmiştir. Kurak yıllarda sırta ekimin birçok kültür bitkisinde nem muhafazası yönünden olumlu bir çevre oluşturduğu bildirilmektedir [17].…”
Section: Başakta Tane Sayısunclassified